Pengaruh Penyajian Laporan Keuangan, Aksesibilitas Laporan Keuangan Terhadap Transparansi dan Akuntabilitas Laporan Keuangan Pemerintah Daerah Kabupaten Boyolali - Aprianti, Dian (2016)
This study aimed to analyze the data and to prove the influence of presentation of financial statements, financial statements accessibility to the transparency and accountability of the Regional financial statements in Boyolali The sampling method using saturated sampling method (of all populations distributed questionnaires). The number of respondents who participated in this study were as many as 45 people. Techniques and methods of data analysis used in this study using the multiple linear regression analysis with SPSS 21. The results showed that the presentation of financial statements, financial statements accessibility positive effect on transparency and accountability in the area of financial reporting. Keywords: Regional Financial Statements, Financial Statements Regional Accessibility, Transparency and Accountability Regional Financial Statements